Rasfaz Enterprise / Muhammad Akram Lokman ... [et al.] - Lokman, Muhammad Akram; Saifulrizal, Adriana Batrisyia; Mohd Tarmizi, Nur Syahira Syazwana; Saleh, Siti Zulaikha; Mohd Yusof, Nur Fatin Nabilah; Abdul Rahim, Rabiatul Athirah (2021)
Rasfaz Enterprise sells and supplies to customers and consumers a variety types of frozen pizza. The company offers a variety menu of frozen pizza for pizza lovers. Our target customers and consumers come from all levels of income in which everyone can afford. We target people like busy office workers, students, teachers, lecturers, single parents and also foreigners who stayed in Malaysia. We also want to promote our business as Bumiputera businesses tothe locals and also to the foreigners who stayed in Malaysia. Rasfaz Enterprise was located at Lorong Iks Juru 8, Taman Perusahaan Ringan Juru, 14100 Simpang Ampat, Pulau Pinang. Simpang Ampat is an area that is not packed or busy as much as in the town. Buying our product could also save time because our pizza just needs to heat up for only 180seconds (3 minutes). This frozen pizza was served in the right size and it suited the taste of Malaysian people. Not only that, we target people like foreigners because we want to promote the uniqueness menu of Malaysian people. For instance, we provide a variety of pizza flavour such as durian cheese, sambal bilis, meat lovers and seafood. The management of Rasfaz Enterprise be made up of 6 workers which is Rabiatul Athirah, Siti Zulaikha, Muhammad Akram, Nur Fatin Nabilah, Nur Syahira Syazwana and Adriana Batrisyia. All of them have experience in finance, businesses, sales, marketing and also expertise in accounting. These six partners will be held accountable together even though different duties of partners. Rasfaz Enterprise’s frozen pizza is a new product that has never been produced before due to the uniqueness flavour and taste. With these strategies, it could help our business to stay focused on business growth, mission and organization’s objectives.